1996
DOI: 10.1111/j.1467-9477.1996.tb00393.x
|View full text |Cite
|
Sign up to set email alerts
|

The 1994 EU Referendum in Norway: Continuity and Change

Abstract: In the 1994 EU referendum a majority of Norwegian voters rejected membership in the European Union. The outcome contrasts with victories for membership in the corresponding referendums in Austria, Finland and Sweden. The article reports a preliminary investigation of factors relating to the support for “no”. Analysis of aggregate data (representing 435 municipalities) and survey data demonstrates the importance of traditional cleavages as well as new cleavages for the vote. The no‐vote was strongest in norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 6 publications
0
17
0
1
Order By: Relevance
“…As it did in 1972, the EU issue in 1994 revitalized the otherwise declining cleavages in Norwegian politics (Pettersen et al, 1996;Sogner and Archer, 1995).…”
Section: Cleavages and The European Votes: An Analysis Of Survey Datamentioning
confidence: 95%
“…As it did in 1972, the EU issue in 1994 revitalized the otherwise declining cleavages in Norwegian politics (Pettersen et al, 1996;Sogner and Archer, 1995).…”
Section: Cleavages and The European Votes: An Analysis Of Survey Datamentioning
confidence: 95%
“…Territorial, cultural, and economic cleavages can also be used to explain the vote during the referendums on EU membership. Other cleavages, such as gender and sector of employment, have also been linked to referendum voting, with women and those in the public sector more likely to vote no (Pettersen, Jenssen, and Listhaug 1996;Gilljam, 1996;Ringdal and Valen, 1998).…”
Section: Party Cues and The Votementioning
confidence: 97%
“…In a detailed study in Norway, the effect of party identification on the vote has been measured in a multivariate model (Pettersen, Jenssen, and Listhaug, 1996). After controlling extensively for a variety of cleavages, the research demonstrated that party support had a significant impact on the referendum vote.…”
Section: Party Cues and The Votementioning
confidence: 99%
See 1 more Smart Citation
“…These links were still intact 30 years later. Attitudes towards the EU were related to several cleavages (Pettersen et al, 1996;Bj0rklund, 1997: ch. 6).…”
Section: The European 'Issue'mentioning
confidence: 99%